DEVELOPMENT OF A METHODOLOGY FOR MODELING THE STATE OF THE WATER ECOSYSTEM BASED ON THE METHODS OF ECOLOGICAL STOICHIOMETRY, TAKING INTO ACCOUNT THE ENERGY APPROACH - ANDREEV, VIACHESLAV; SLUCHAK, Oleksandr; SLUCHAK, Olena; ALEKSEEVA, Anna; KRYSINSKA, Diana (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article develops a methodology for modeling the state of the food chain of the aquatic ecosystem in terms of biomass growth of producers based on ecological energy stoichiometry. The research is based on a number of sinusoidal functions developed during the simulation of the monthly solar energy arrival per unit area by latitude. The average forecast indicator of energy input for southern Ukraine of 2518 MJ/m2 is very close to the results of similar applied measurements in Odesa. For modeling, the average latitude for Ukraine is 48°23', the average inclinations of the sun for each of the 8 months according to the astronomical calendar (about 14), as well as the average duration of a sunny day, and the angle of incidence and reflection of the sun's rays on water are determined based on them, taking into account only the angle of incidence at noon, and changes during the day (the angle of reflection ranges from 17.5 in June to 29.26 in September). Correction coefficients for latitude were derived, the percentage ratio of days with cyclonic weather, due to which there is an increase in reflection due to cloudiness and waves, was calculated - 638 hours and 30 minutes. The efficiency of photosynthesis for the main groups of phytoplankton organisms was calculated, which is 1.98 % for Chlorophyta, 2.38 % for Cyanophyta, 1.96 % for Euglenophyta and 1.65 % for all others. The overall average efficiency of photosynthesis was thus 1.83 %. Taking into account the area of ​​the water mirror, the arrival of energy, reflection, scattering and absorption. Taking into account the efficiency of photosynthesis, a stoichiometric simulation of the increase in biomass of producers was carried out. The potential of carbon dioxide deposition is 2.6 kg/m2 per year, oxygen release is 1.92 kg/m2, and biomass growth is 1.8 kg/m2. This is the maximum potential. The study is supplemented by derived correction factors based on energy and toxicological indices of environmental safety, ORP and the Redfield ratio. This gives a real total energy per square meter of 12335.66473 kJ, biomass growth of 773.1266184 g/m2. The predictive model yields 577.6 kg/ha per year of fish, which is close to the value of natural bioproductivity for herbivorous fish (505 kg/ha). At the stage of food chain analysis, it is proposed to additionally use the deduced regularity of the effect of salinity on the growth of macroliths and correction coefficients of fish productivity for different soils. The basis for automation and local modeling is laid.
Keywords: ecological stoichiometry; modeling of biocenoses; efficiency of photosynthesis; albedo of water bodies; energetics of water ecosystem; bioproductivity of fish